2015
DOI: 10.4103/0366-6999.151106
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Study of Sporadic Burkitt Lymphoma in Children

Abstract: Background:Non-Hodgkin lymphoma is the fourth most common malignant tumors in children, Burkitt lymphoma (BL) accounts for 30–50% of all pediatric lymphomas. The aim of this study was to investigate the clinicopathologic features, immunophenotype, Epstein-Barr virus (EBV) infection and c-myc gene rearrangement of sporadic BL in children.Methods:Ninety-two cases of pediatric BL were retrospectively analyzed for clinical features, immunohistochemistry, EBV-encoded RNA (EBER) status by in situ hybridization and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…For example, Huang et al . 49 found low albumin and MUM1 expression to be highly correlated with increased mortality in BL. Another study found BCL-6 expression to be associated with better survival.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, Huang et al . 49 found low albumin and MUM1 expression to be highly correlated with increased mortality in BL. Another study found BCL-6 expression to be associated with better survival.…”
Section: Discussionmentioning
confidence: 83%
“…Several genetic markers and laboratory parameters have been identified as important prognostic markers but were not available for our analyses. For example, Huang et al 49 found low albumin and MUM1 expression to be highly correlated with increased mortality in BL. Another study found BCL-6 expression to be associated with better survival.…”
Section: Cancer Epidemiologymentioning
confidence: 99%
“…Although CD10-positivity can be seen in DLBCL NOS, the neoplastic cells are usually Bcl-2 positive and display a slightly lower Ki-67 proliferative index compared with BL that is close to 100% 7. Although the present case was not assessed for gene rearrangement and MYC immunohistochemical staining, there are cases in the literature without information about MYC gene rearrangement, and according to clinical, morphological and immunohistochemical characteristics were diagnosed as BL 20. It is well recognized that chromosomal translocations in the MYC oncogene are the biological hallmark of BL, but also may be present in other B-cell lymphomas; in this sense, when the morphological characteristics are compatible with BL, and the immunohistochemical findings show positivity for MYC and Bcl-2, it is recommended to perform molecular tests in the search for gene rearrangements to rule out DHL or THL 1 , 11 , 16.…”
Section: Discussionmentioning
confidence: 65%
“…8,9 BL is the most common histological subtype as mentioned in literature and as manifested in this study and commonest presenting sign decribed in literature was abdominal mass as it is evident in this study as well. 10,11 NH-Lymphomas are rapidly growing tumors and patients present late with widespread disease, majority of patients (>90%) in this study also presented in advanced stage i.e. in stage, 3 or 4.…”
Section: Discussionmentioning
confidence: 69%